Diagnostic evaluation and management of obscure overt haemorrhage in a Jehovah’s witness patient: a case report and review of the literature - Menon, Rahul (International Surgery Journal, 2024)
Metastasis of cutaneous malignancies to the small intestine is rare with only up to 4.7% found in antemortem patients. The most common presenting symptoms is obstruction or intussusception whilst obscure overt haemorrhage is rare. Acute haemorrhage progressing to hypovolaemic shock is a serious and preventable issue and can be prevented by addressing the underlying cause and with the judicious use of blood products. However, in certain populations such as Jehovah’s witnesses, the administration of blood products is forbidden. In the acute surgical patient who was in acute haemorrhagic hypovolaemic shock, blood-less transfusion methods included early identification of wishes, diagnosis and treatment, intraoperative cell salvage and normovolaemic haemodilution, antifibrinolytics, intraoperative sealants, and optimal surgical technique. This report described the diagnosis and management of the case of a 62-year-old male patient who presented with severe obscure overt haemorrhage and a haemoglobin nadir of 3.7 g/dl who declined blood products. This patient had unremarkable imaging findings on CT and no embolization target despite a jejunal mass with active arterial blush. Diagnostic laparoscopy with on-table push enteroscopy identified an ulcerated jejunal lesion that was subsequently resected. Histopathological assessment of the specimen revealed a diagnosis of metastatic melanoma. The patient ultimately received palliative chemotherapy and immunotherapy. To improve early diagnosis of small-bowel metastases, a combination of imaging techniques is recommended for patients with a history of cutaneous melanoma who have obscure gastrointestinal bleeding, anaemia, and other non-specific abdominal symptoms.